2021
DOI: 10.1017/dmp.2021.257
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy of Health-Care Workers: Another Challenge in the Fight Against COVID-19 in Istanbul

Abstract: Objective: Healthcare workers (HCWs), are often seen as the most reliable source of vaccine-related information for their patients; nevertheless, various studies show that HCWs experience vaccine hesitation. In this study, the aim was to determine the reasons for vaccine hesitation among HCWs working in a large public hospital and its affiliated units in Istanbul. Method: A descriptive method for collecting qualitative data was designed for this study. The data of the HCWs was analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
(26 reference statements)
4
11
0
Order By: Relevance
“…Moreover, a systematic review on HCW’s vaccine attitude and related factors by Li et al also highlighted that females had higher vaccine hesitancy [ 40 ]. In the same way, previous studies have found that male HCWs were more likely to vaccinate than female HCWs [ 21 , 24 , 41 ].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, a systematic review on HCW’s vaccine attitude and related factors by Li et al also highlighted that females had higher vaccine hesitancy [ 40 ]. In the same way, previous studies have found that male HCWs were more likely to vaccinate than female HCWs [ 21 , 24 , 41 ].…”
Section: Discussionmentioning
confidence: 54%
“…According to several studies, males had a higher risk of COVID-19 complications, infectivity, and death [ 24 , 42 ]. Furthermore, it has been hypothesized that this is owing to worries about side effects such as infertility, major side effects that render them unable to care for their family, higher sensitivity to media myths and disinformation, and dread of receiving the vaccination while pregnant [ 21 , 41 ]. Previous studies have suggested that tailored communication strategies are needed to increase the uptake rate of COVID-19 vaccines among HCWs [ 10 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…İkiışık et al [27] showed that male doctors had a higher acceptance rate than females. Yilmaz et al [31] briefly reported that fear and lack of confidence were the most cited reasons related to vaccine hesitancy among HCWs. In addition to the average age and professional experience, pregnancy and breastfeeding were the most common reasons for vaccine hesitancy among females.…”
Section: Discussionmentioning
confidence: 99%
“…Although symptoms and the effects of coronavirus on health have been excessively covered by media 29 , many people, including healthcare workers, experienced vaccine hesitation due to a lack of confidence in the vaccines 30 , 31 . Moreover, misinformation spread through social media 31 , and being exposed to them due to the overuse of electronic devices during the lockdowns left people anxious, fearful, and ultimately hopeless 32 .…”
Section: Introductionmentioning
confidence: 99%